Fine needle aspiration cytology-based spectrum of salivary gland lesions at a teaching institute in north India - N. Satarkar, Rahul; Sangwaiya, Ashok; Singh, Pawan; Kalhan, Shivani; Sharma, Puja; Saini, Neerav (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Salivary gland swellings can occur because of inflammation, cyst or neoplastic process. Neoplasms of salivary glands are relatively rare comprising less than 2% of all human tumors. Prevalence of salivary of gland lesions differ from place to place. There are more than 30 morphologically different types of salivary gland neoplasms; majority of which can be diagnosed on fine needle aspiration cytology with expertise. Material and methods: This was a retrospective observational study spanning over 5 years carried out in the department of Pathology, Shaheed Hasan Khan Mewati Government Medical College, Nalhar. Hundred and forty-seven patients with salivary gland swelling were included in the study. Result: Benign salivary gland neoplasm was the most common lesion (54.42%) followed by inflammatory lesions (20.40%). Pleomorphic adenoma (90%) was the most common benign tumor affecting predominantly female patient and mostly involving the parotid gland. Mucoepidermoid carcinoma was the most common malignant tumor (36.85%) followed by poorly differentiated carcinoma (26.31%). Benign tumors were more common in females, whereas malignant tumors occurred more frequently in males. Conclusion: Fine needle aspiration cytology is fast, reliable and relatively accurate method to give tissue-based diagnosis of salivary gland swellings. It helps the clinician to plan the treatment modality for the patients in short time.